MODEL ISMAIL R. AL-FARUQI: ISLAMISASI ILMU PENGETAHUAN - Riswan; Amril M; Yenni Kurniawati (STKIP Subang, 2026)
The development of modern science dominated by Western paradigms often separates scientific knowledge from religious values. This condition creates various problems in the field of education and social life, especially for Muslims who possess their own system of values. Such separation has led to the emergence of a dualism of knowledge between religious sciences and modern sciences, which influences how people understand the reality of life. Therefore, an approach is needed to integrate modern scientific knowledge with Islamic values. This study aims to analyze the concept of the Islamization of knowledge proposed by Ismail R. Al-Faruqi and its relevance to the development of science and Islamic education. This research uses a qualitative approach with a library research method. The data were obtained from various relevant literature sources, including books, scientific journal articles, and academic works discussing Ismail R. Al-Faruqi’s ideas on the Islamization of knowledge. The data collection technique was carried out through documentation studies, while the data were analyzed using a descriptive-analytical method. The results of the study indicate that the Islamization of knowledge according to Al-Faruqi is an effort to integrate modern science with Islamic values based on the principle of tawhid. This concept emphasizes the reconstruction of scientific disciplines to align with the Islamic worldview and eliminate the dualism in the education system. Therefore, the Islamization of knowledge can become an important approach in building a more holistic scientific paradigm oriented toward human welfare.